Os projetos pedagógicos de cursos de licenciatura em química no estado de Goiás: do conhecer ao construir - Mesquita, Nyuara Araújo da Silva (2010)
With the development of this research we seek to investigate how the relationships and interactions between the constituent elements of the pedagogical courses projects (PPC) of Chemistry teacher training Courses in the Goiás state, Brazil. We used as a research method a discursive textual analysis aimed at fragmenting documents examined in units of analysis, relations between unit the categorization process and build a new text that presents the new understandings of the phenomenon studied. We question whether, in the documents, the relationships and interactions stabilished enable or provide a training thatvincludes the current guidelines for teacher training. Identified positive conceptions about the vision of science, lack of clarity regarding the professional profile to be formed and found the identity crisis of the university when you try to justify theire actions relating to the needs of the labor market. We analyze the contradictions in relation to issues of interdisciplinarity, training by research and through use of information technology and communication. We studied in detail the PPC in Chemistry teacher training Courses, we re-designed our views and we give as a subject/researcher/teacher in a process of continuing education teacher's own trainer. This change enabled us to participate in the drafiting of a new PPC seekinh help to produce a document that had minimized the contradictions received by us on other PPC. We therefore propose that the conscious participation in the construction and preparation of the PPC requires the understanding of the intentions of which are governed these documents constituded as drivers of the paths chosen for the implementation of the pedagogical and identity of a stroke.